Business model analysis and determination of production cost of Micro, Small and Medium Enterprises (MSME) Product Businesses Talok Village, Turen Distric, Malang with Business Model Canvas (BMC) - Fatchiyah Fatchiyah; Nia Kurniawan; Ary Mustofa Ahmad; Irfan Mustafa; Lidwina Faraline Triprisila; Rista Nikmatu Rohmah; Anna Safitri; Nia Kurnianingsih; Tri Wahyu Nugroho (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2018)
Talok is a partner district with economic conditions that have developing status according District Development Index values. The developing status related with susceptible of economic shocks, natural disasters and social conflicts will be effect to underdeveloped district. This Community Empowerment Program is purpose to develop Micro, Small and Medium Enterprises (MSME) product businesses can expect to income increasing of enterprise through the Business Model Canvas (BMC) approach. Mapping survey of local potentials from partner district was observed to achieve the success of community service activity. In this survey, we collaborate with MSME partners are (1) Samiler Crackers MSME group, (2) Cassava Chips MSME group, (3) Lempeng Crackers MSME group. The data was analyses using descriptive and qualitative method by using the in-depth interview in collecting primary data needed during the research process. The BMC analysis on each element of business model canvas could improve the service quality, marketing activity, infrastructure and financial ability. Business model canvas focuses on business ideas to create value in the business. In addition, the cost of production calculation is very important for selling price determination of the product to avoid the losses condition.